PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KARYAWAN DI RUMAH SAKIT WIDODO NGAWI TAHUN 2018 - Prayitno, Suhadi (STIKes Maharani Malang, 2019)
Work environment was one of efficacy factor in doing a work, but also can result an unsuccess in work execution. ( Kurniasari, 2014). Problems which often happened was work environment and small compensation and also employees satisfaction in doing this work. The aim of this research was analyse influence of work environment and compensation to employee satisfaction at Widodo Hospital Ngawi 2018. This Research type was quantitative with approach of cross sectional. This Research Sampels are 58 employees at Widodo Hospital Ngawi. Technique intake of sampel by used poportional random sampling. Data processed method by used univariat, bivariate, Chi Square and Regresi logistic. Result of this Research was result from work environment to satisfaction there was significant influence showing calculation by chi square of work environtment to satisfaction of its result employees with value of sig 0,004, calculation of chi Square compensationi to satisfaction of its result employees 0,003 and calculation of logistic regression work environmental result of signifikan 0,998 above > 0,05 Ho1 there was not influence of wor environment to employees satisfaction. Result bycalculation of result of significan 0,005 under < 0,05 concluding if its result of Ha there was influence of compensation to employees satisfaction. So that its conclusion there was influence of compensation with employees satisfaction.Suggestion which researcher recommend was expected to hospital to continue improve peaceful and balmy work environment for employees. So that employees can work better, and also improve discipline to employees so can on timed the schedule